2015
DOI: 10.1099/mic.0.000080
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine in bacterial physiology and metabolism

Abstract: Carnitine is a quaternary amine compound found at high concentration in animal tissues, particularly muscle, and is most well studied for its contribution to fatty acid transport into mitochondria. In bacteria, carnitine is an important osmoprotectant, and can also enhance thermotolerance, cryotolerance and barotolerance. Carnitine can be transported into the cell or acquired from metabolic precursors, where it can serve directly as a compatible solute for stress protection or be metabolized through one of a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(145 citation statements)
references
References 151 publications
(175 reference statements)
2
137
0
Order By: Relevance
“…We confirmed that A. baumannii uses carnitine as sole carbon and energy source. This together with the abundance of carnitine in the human host (Meadows & Wargo, ) suggests that carnitine is important for metabolic adaptation of A. baumannii to the human host. However, this might only be one physiological benefit of carnitine for A. baumannii .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed that A. baumannii uses carnitine as sole carbon and energy source. This together with the abundance of carnitine in the human host (Meadows & Wargo, ) suggests that carnitine is important for metabolic adaptation of A. baumannii to the human host. However, this might only be one physiological benefit of carnitine for A. baumannii .…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of both choline and carnitine by a classical member of the BCCT family is quite unique and without precedence. Carnitine transport and metabolism have already been thoroughly studied in different bacteria such as Pseudomonas aeruginosa and in members of the Enterobacteriaceae (Meadows & Wargo, ). In P. aeruginosa, carnitine is imported by an ABC transporter and can be used as sole carbon and nitrogen source but also plays a role in osmoprotection and virulence factor induction (Chen, Malek, Wargo, Hogan, & Beattie, ; Kleber, Schöpp, Sorger, Tauchert, & Aurich, ; Lucchesi et al, ; Wargo & Hogan, ).…”
Section: Discussionmentioning
confidence: 99%
“…The strongest signal was observed for ornithine ( p -value = 0.008), which is also significantly associated with tooth mobility ( p -value = 0.012). The remaining metabolites also included 3-dehydrocarnitine, ranked fifth ( p -value = 0.029), which is consumed by gram negative and positive bacteria in either aerobic or anaerobic environmental insults or as a sole carbon, nitrogen and energy source [24].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, bile acids are metabolites of cholesterol that are produced by vertebrates and thus unlikely to be encountered outside of the host. While the metabolite L-carnitine is made and used in organisms spanning the tree of life, it is particularly concentrated in animal tissue and especially red meat, and cannot be further catabolized by humans [43], making it available to intestinal microbes. Bile acid transformation by gut commensals is a well-established function of the gut microbiome, with complex influences on health (reviewed in Staley et al [44]).…”
Section: Using Body Sites As a Control Allows Us To Differentiate Genmentioning
confidence: 99%